Familial adenomatous polyposis in a 5 year old child: a clinical, pathological, and molecular genetic study. Issue 2 (February 1996) - Distante, S; Nasioulas, S; Somers, G R; Cameron, D J; Young, M A; Forrest, S M; Gardner, R J
Abstract : A girl aged 5 years 8 months presented with rectal bleeding; her father had had familial adenomatous polyposis (FAP) and a colectomy at the age of 23. Endoscopy showed extensive polyposis and she had a colectomy. The proband and her father had the common codon 1309 5 bp deletion APC mutation. This mutation predisposes to early onset of FAP, and consideration needs to be given to having molecular testing of at risk members of these families done in childhood.